Sodium tetratungstate/tungsten oxide films prepared with dodecyltrimethylammonium chloride as structuring agent - Soares de Moura, Diego; Santos Garcia, Irene Teresinha (Revista Eletrônica Científica da UERGS, 2022)
The multiple forms of structuring transition metal anions in solution are important aspects to be taken into account in obtaining oxides of these metals by the sol-gel method. The formation of polyanions in aqueous media can produce a variety of structures in the solid state. Films were obtained through sol-gel method with sodium tungstate as precursor and dodecyltrimethylammonium chloride (DTAC) as structuring agent, after calcined at 700 °C in air. The films, structured as nanospheres, were composed mainly of triclinic sodium tetratungstate and monoclinic tungsten oxide. The cationic surfactant interacts in aqueous media with the precursor, affecting the obtained films' final morphology, without affecting their crystal structure. Their photocatalytic properties were also evaluated.